Translation and validation of Persian version of resilience evaluation scale (RES): A cross-cultural methodological research - Hamidreza Aghababaeian; Abbas Ostadtaghizadeh; Armin Zareian; Miranda Olff; Christianne van der Meer; Ladan Araghi Ahvazi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The Resilience Evaluation Scale (RES) is a new, free and short self-report questionnaire for measuring psychological resilience. This study aims to translate and assess the psychometric properties of the RES. MATERIALS AND METHOD: In the present methodological study, after the translation process, face and content validity were conducted through qualitative and quantitative methods. To determine the construct validity, exploratory and confirmatory factor analysis (CFA) was used, and for the reliability, Cronbach's α test and inter-counter coefficient test were calculated. Persian version of the Connor-Davidson Resilience Scale was used to determine the convergent validity of the questionnaire. RESULTS: Results show that the face and content validity of 9 items of RES were acceptable and they were all approved [Impact scores (IS) >1.5, S-CVI/Ave = 0.97, I-CVI = 0.93]; the Internal consistency of the scale was confirmed by the Cronbach's α coefficient (0.82) and McDonald's omega (0.83). The reliability of the scale also was confirmed by the Spearman's correlation coefficient and intra-group correlation coefficient (ICC), with results obtained above 0.8 for all items. The factor analysis identified two factors that accounted for about 56% of the variance. Also, the CFA model fitted well according to the results of the fitting indices (RMSEA = 0.084, CFI = 0.98, SRMR = 0.064, and TLI = 0.97). In addition, the convergent validity of the scale was equal to 0.65 (P < 0.001). CONCLUSION: Development of a valid and reliable psychological resilience scale may bring great benefits to the Persian society. Our findings suggest that the Persian RES has good psychometric properties, and it may serve as a valuable instrument in research and clinical practice.